Evaluation of phrenic nerve stimulation trigger lag and synchronization in different modes of ventilation - Bentley, Ishmael; Jocewicz, Frank T.; Johnson, Bruce D.; Mehta, Hitesh P. (Frontiers in Physiology, 2024)
Phrenic nerve stimulation is currently being investigated for the prevention of diaphragm atrophy in patients with mechanically supported breathing. Patients receiving breathing support from mechanical ventilation are at risk of mismatches between respiratory demand and ventilator support. Our objectives were to determine if a novel phrenic nerve stimulation device provided stimulation during inspiration as intended and did not exacerbate any potential discordances. A benchtop electromechanical simulation model was developed to validate phrenic nerve stimulation with simulated breathing. The phrenic nerve stimulation device was evaluated with a mechanical ventilator attached to a breathing simulator. The trigger ratio and time lag between phrenic nerve stimulation and mechanical ventilation was measured for multiple disease and ventilator parameters. For the 1:1 breath trigger ratio test, 99.79% of intended stimulation breaths received stimulation at the correct time. For the 1:4 breath trigger ratio test, 99.72% of intended stimulation breaths received stimulation at the correct time. For trigger lag times for the inspiratory and expiratory phases, the mean inspiratory lag was 36.10 ± 10.50 ms and 16.61 ± 3.61 ms, respectively. The following discordance scenarios were evaluated in conjunction with simulated phrenic nerve stimulation: asynchrony-false trigger, dyssynchrony-early trigger, dyssynchrony-late trigger, dyssynchrony-early cycling, dyssynchrony-late cycling. Testing demonstrated none of these discordances were exacerbated by the simulated phrenic nerve stimulation. The novel phrenic nerve stimulation device delivered electrical stimulation therapy as intended and did not exacerbate any simulated discordances.